2007
DOI: 10.1158/0008-5472.can-06-4625
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Activity of Epidermal Growth Factor Receptor Kinase Mutant Alleles Is Enhanced by the T790M Drug Resistance Mutation

Abstract: Activating mutations in the epidermal growth factor receptor (EGFR) characterize a subset of non-small cell lung cancers (NSCLC) with extraordinary sensitivity to targeted tyrosine kinase inhibitors (TKI). A single secondary EGFR mutation, T790M, arising in cis with the primary activating mutation, confers acquired resistance to these drugs. However, the T790M mutation is also detected in the absence of drug selection, suggesting that it may provide a growth advantage. We show here that although T790M alone ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
100
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 41 publications
9
100
0
1
Order By: Relevance
“…2B). Such enhancement of EGFR phosphorylation and activity by T790M in double mutants has also been showed by other researchers (34,35). However, detailed clinical studies are necessary to ascertain whether the in vitro differences would translate into clinically observable differences in the patients' responses.…”
Section: Discussionsupporting
confidence: 66%
“…2B). Such enhancement of EGFR phosphorylation and activity by T790M in double mutants has also been showed by other researchers (34,35). However, detailed clinical studies are necessary to ascertain whether the in vitro differences would translate into clinically observable differences in the patients' responses.…”
Section: Discussionsupporting
confidence: 66%
“…Of the four mutant EGFR cell lines we examined, all contain additional genetic alterations that boost EGFR signaling, and some of these changes also confer resistance to EGFRIs. For example, both HCC827 and H3255 exhibit amplification at the EGFR locus, dramatically enhancing EGFR signaling, whereas H1975 carries the T790M mutation that, when combined in cis with L858R or del746-750 mutations, boosts EGFR signaling (26). The T790M mutation also confers resistance to gefitinib by blocking drug binding (SI Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The double mutations not only confer resistance to gefitinib/erlotinib but also result in markedly enhanced catalytic kinase and oncogenic activity (Mulloy et al, 2007). Emerging evidence suggests that the T790M 'gatekeeper' mutation may exist in lung tumours before EGFR-TKI therapeutic selection (Bell et al, 2005;Godin-Heymann et al, 2007), partly due to its enhanced oncogenicity, and accounts for the adverse clinical course and outcome in gefitinib/erlotinib-resistance lung cancers after a course of rapid TKI selection. Interestingly, we found that H1975 cells co-express EGFR and MET at high level, although without any MET genomic amplification, and were capable of serum-independent constitutive MET activation.…”
Section: Discussionmentioning
confidence: 99%